Does Facilitating Conditions have an Effect on AI Adoption in Financial Services? Exploring Further Impact on Digital Financial Inclusion - Mr. Vaibhav Sinha; Dr. Ajit Kumar (The Bioscan, 2024)
Objectives: This paper studies the impact of the role of facilitating conditions on the adoption of artificial intelligence in financial services, further exploring the impact on digital financial inclusion. Methods: The research model used is the modified Unified Theory of Acceptance and Use of Technology (UTAUT) model. Independent variables likely, performance expectancy, effort expectancy and facilitating conditions and their effect on adoption of AI in financial services has been researched using questionnaire method. Further the impact of adoption of AI in financial services impact on digital financial inclusion is studied. Judgemental sampling technique was used and the data was analysed using SPSS and AMOS software. Findings: Results reveal that performance expectancy, effort expectancy and facilitating conditions have a positive influence on the adoption of artificial intelligence on financial services. Also, it was found out that the adoption of artificial intelligence on financial services has a significant positive impact on digital financial inclusion. These findings shall be helpful in policy and strategy formulation of the government and corporate and fintech firms in accordance to the use and adoption of artificial intelligence in the financial services industry and increase the financial inclusion of a population using digital methods.